1979
DOI: 10.1111/j.1399-0004.1979.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Distal trisomy 17q

Abstract: A 3‐year‐old, male patient with trisomy 17q231qter due to a paternal t(5;17)(p151;q231) is compared to three other patients reported in the literature who are trisomic for the same segment due to a familial t(17;21)(q23;q22). The features common to the four patients are: profound mental retardation; dwarfism; frontal bossing and temporal retraction; narrow squinty eyes; thin lips with overlapping of the lower lip by the upper lip; very low‐set and abnormal ears; cleft palate; and hyperlaxity of the ligaments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In the literature, there have been only 12 reported live-born cases of partial trisomy for the distal region of 17q. Most of these were due to reciprocal translocations, which were derived either from one of the parents (Berberich et al 1978, Turleau et al 1979, Yamamoto et al 1979, Gallien et al 1981, Shawe et al 1983, Naccache et al 1984, Bridge et al 1985, Parcheta et al 1985 or from a de n o w occurrence (Fryns et al 1979). Another case of trisomy 17q was reported recently, and was interpreted to be a result of tandem duplication of the sole 17q25 band, especially on the grounds of the clinical features present in the patient (Orye & Van Bever 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there have been only 12 reported live-born cases of partial trisomy for the distal region of 17q. Most of these were due to reciprocal translocations, which were derived either from one of the parents (Berberich et al 1978, Turleau et al 1979, Yamamoto et al 1979, Gallien et al 1981, Shawe et al 1983, Naccache et al 1984, Bridge et al 1985, Parcheta et al 1985 or from a de n o w occurrence (Fryns et al 1979). Another case of trisomy 17q was reported recently, and was interpreted to be a result of tandem duplication of the sole 17q25 band, especially on the grounds of the clinical features present in the patient (Orye & Van Bever 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The subsequently reported cases of a similar chromosome abnormality have shown that trisomy for the distal part of 17q is associated with a clinically recognizable syndrome (Shawe et al 1983, Naccache et al 1984, Bridge et al 1985. Most of the reported cases were inherited from parental translocations (Berberich et al 1978, Turleau et al 1979, Yamamoto et al 1979, Gallien et al 1981, Shawe et al 1983, Naccache et al 1984, Bridge et al 1985, Parcheta et al 1985. Two de novo cases have been reported, one resulting from translocation of 17q/21q (Fryns et al 1979) and the other from tandem duplication (Orye & Van Bever 1985).…”
mentioning
confidence: 99%
“… NA, not applicable; +, feature present; −, feature absent. Babovic‐Vuksanovic et al ; Berberich et al ; Kelly et al ; Bridge et al ; Caine et al ; Fryns et al ; Gallien et al ; Naccache et al ; Ohdo et al ; Orye et al (1985); Robb et al (1987); Serokin et al ; Shimizu et al ; Turleau et al ; Yamamoto et al . …”
Section: Discussionmentioning
confidence: 99%
“…Trisomy of the distal portion of long (q) arm of chromosome 17 is a rare but recognized syndrome, with approximately 20 similar cases reported to date. The common characteristic features reported among individuals with distal 17q trisomy overlap, and include microcephaly, short stature, distinct facial features, short and webbed neck, low posterior hairline, rhizomelia, polydactyly, syndactyly, and others . Both de novo and inherited cases have been reported .…”
Section: Introductionmentioning
confidence: 99%